MANTRA BUGIS DESA TANJUNG SAMALANTAKAN KAJIAN JENIS, FUNGSI, DAN MAKNA - Andi Muhammad Yahya (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2016)
Mantra Bugis village of Tanjung Samalantakan Study Type, Function, and Meaning. Mantra Bugis village of Tanjung Samalantakan the wording contain magical powers. They strongly believe in the power contained in a magical spell to realize its objectives into concrete manifestation. The purpose of this research is to describe the type, function and meaning of the mantra Bugis Village Tanjung Samalantakan. This research is a field research. The method used is descriptive method. The data in this study a spell Bugis obtained from interviews and literature. Data was collected by noting and recording the spoken mantra informant. From the research that the type of spell Bugis namely (1) the customs spells, spells of treatment, Decoy spell, and personal protective spells. (2) function spells Bugis them to build houses, to save money, easy childbirth, to treat pain, to call a sweetheart, for subduing wife, for courage, for personal protection, to increase the strength of the blow, (3) the meaning of mantra Bugis. First, with regard to human relationships with. Secondly, with regard to man's relationship with his neighbor. Third, with regard to man's relationship with himself cover in case the value of self, and the fourth, with regard to man's relationship with other creatures.